A educação confessional face ao princípio da laicidade: uma análise da pedagogia adventista em Belo Horizonte - Daniel Antunes Ataides (2011)
The masters dissertation under the title in epigraph addresses the confessional education provided in Brazil by protestant groups, like the Adventist educational system. The advent of Republic breaks with the official character of a state religion and favors the presence of protestant groups that equate in relation to all other faiths, what applies to the exercise of the private systems at the formal education. The research is supported on Durkheims theories due to his position in favor of the secularism of State of the education, even though he considers Religion as an important analysis category and the religious institution as an important historical aspect for the construction of a project of school education. The study is divided in two parts: documentary research and field research. The documentary research had as objective to situate confessional education on the context of the State laicity and get to know the seventh day Adventists as a religious group and as agents in the field of school education. The field research sought to establish a bound between the content found in the documents and the pedagogical practice, as well as the school routine, perceived in the observations carried out in the educational institution. For such, we chose the Colégio Adventista de Belo Horizonte, - CABH [Adventist College of Belo Horizonte, in the state of Minas Gerais, Brazil], the largest institution of the system in Belo Horizonte. Observations at the class at of the school routine, questionnaires for voluntary answer and semi-structured interviews were the procedures adopted for data collection. Acknowledging the State and teaching laicity as a construction in process and religion as a outstanding presence at the State and education history, the research provided interesting perspectives of analysis of the interaction forms between the institutions involved, taking into consideration aspects as: curricula, school-family relationship, quality concept and representations son public education system. As the State has the guardianship of education, besides undertaking the public school education, also establishes the rules for the functioning of the education offered by private systems. The supposed and eventual mismanagements of an institution upon the other constitute the mail theme in question.